2005
DOI: 10.1024/0301-1526.34.4.235
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatility index is better than ankle-brachial Doppler index for non-invasive detection of critical limb ischaemia in diabetes

Abstract: The pulsatility index is a better noninvasive technique than the ankle-brachial Doppler index or the systolic ankle pressure to assess critical limb ischaemia in diabetic polyneuropathy. A pulsatility index < 1.2 at the ankle arteries is a reliable criterion for diagnosis of CLI in diabetic patients with polyneuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
1
24
0
2
Order By: Relevance
“…The earliest signs (grey scale) of atherosclerotic disease are thickening of intima and media followed by wall changes (luminal narrowing and soft or hard plaques) and turbulence & flow irregularities on color Doppler flow images [16]. In our study, plaque variants intimal thickening and atheroma were more common in popliteal (18.21% and 17.29% respectively) and superficial femoral arteries (17.68% and 17.29% respectively).…”
Section: Ultrasound Color Doppler Findingsmentioning
confidence: 58%
See 1 more Smart Citation
“…The earliest signs (grey scale) of atherosclerotic disease are thickening of intima and media followed by wall changes (luminal narrowing and soft or hard plaques) and turbulence & flow irregularities on color Doppler flow images [16]. In our study, plaque variants intimal thickening and atheroma were more common in popliteal (18.21% and 17.29% respectively) and superficial femoral arteries (17.68% and 17.29% respectively).…”
Section: Ultrasound Color Doppler Findingsmentioning
confidence: 58%
“…Leoniuk et al found that lower values of pulsatility index were significantly more common in the subgroup of patients with trophic skin changes [12]. Janssen et al demon strated that the pulsatility index is a better marker in non --invasive assessment of critical limb ischemia in diabetic patients with polyneuropathy than the ankle-brachial index [16].…”
Section: Ultrasound Color Doppler Findingsmentioning
confidence: 99%
“…In the literature, Doppler ultrasound flow imaging is the most common method for evaluating the arteries of lower extremities . Janssen et al declared that PI is the best method for the evaluation of critical limb ischemia in patients with diabetic polyneuropathy . All Doppler USG measurements were performed as routine distal lower extremity arterial examination over certain predefined anatomical points.…”
Section: Discussionmentioning
confidence: 99%
“…19 Janssen et al declared that PI is the best method for the evaluation of critical limb ischemia in patients with diabetic polyneuropathy. 24 All Doppler USG measurements were performed as routine distal lower extremity arterial examination over certain predefined anatomical points. For posterior tibial artery the midpoint between medial malleolus and Achilles tendon and for the dorsalis pedis artery the point on the midline of 1 st web, 4 cm proximal to the 1 st MTP joint was used with a standardized leg position and room temperature for all patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the assessment of flow parameters (PSV, EDV, RI, PI) significant correlations were observed for the pulsatility index – lower values were significantly more common in the subgroup of patients with trophic skin changes. Janssen et al demonstrated that the pulsatility index is a better marker in noninvasive assessment of limb ischemia in diabetic patients that the ankle-brachial index [16]. …”
Section: Discussionmentioning
confidence: 99%